Thermodynamic and Kinetic Investigations for the Decomposition of Aqueous Hydrogen Peroxide on MnO2 and PbO Surfaces at Different Temperatures - Abuissa , Hitham. M.; Eleribi , Mohamed. M. (Scientific Journal of University of Benghazi, 2022)
In this study, decomposition reactions were determined and the kinetics of these decomposition reactions were used as an indications process for catalyst. The rate, rate constants and half-lifetimes were determined at different temperatures. Additionally, the values of activation energy were also defined. The kinetics of decomposition reactions were analyzed by first-order equation and rate constants were determined from the slopes of the straight lines of the first-order equation. After that, half- lifetimes were estimated from rate constants, and the activation energy value for reactions was determined from the slopes of straight lines of the Arrhenius equation, where its value was 1.59 kJ/mol for MnO2 and 31.60 kJ/mol for PbO. Furthermore, thermodynamics parameters ΔH# and ΔS# were determined from the slopes and intercepts of linear lines when drawing the Eyring equation. In addition, the values of ΔG# were calculated from values of ΔH# and ΔS#. The temperature influence on the kinetics of the decomposition reactions was within the study plan.